Two new species of Petrocosmea (Gesneriaceae) from Thailand - Middleton, David J.; Triboun, Pramote (Thai Forest Bulletin (Botany), 2014)
Two new species of Petrocosmea section Deinanthera are described, P. pubescens D.J.Middleton & Triboun and P. bicolor D.J.Middleton & Triboun.